Assessment of Agricultural Drought Using Vegetation Condition Index and Vegetation Health Index in Niger River Basin, Nigeria - Muhammad Lawal Abubakar; Muhammad Sambo Ahmed; Auwal Farouk Abdussalam (Department of Geography Education, University of Jember, 2024)
Soil moisture indicates the dryness of the ground surface. This phenomenon is directly tied to vegetation quality and Land Surface Temperature in a specific place. As a result, these characteristics indirectly describe the dryness of the ground surface. This study assessed agricultural drought in Niger River in Nigeria. Data used include MODIS driven MOD13Q1 (NDVI), and MOD11A2 (LST) datasets obtained from Land Processes Distributed Active Archive Center. These datasets were used to compute Vegetation Condition Index (VCI) and Vegetation Health Index (VHI) in Niger River Basin, Nigeria. Additionally, correlation and regression analyses were used to check the relationship between LST and NDVI. Results revealed that the mean NDVI for the year 2002 is 0.494, 0.477 in 2007, 0.468 in 2012, 0.458 in 2017 and 0.430 in 2022. The mean LST in Niger River Basin for year 2002 is 32.28 oC, 32.12 oC in 2007, 32.35 oC in 2012, 33.20 oC in 2017 and 33.41 oC in 2022. For the statistical relationship between NDVI and LST, results exhibited negative correlation, with -0.33 in 2002, -0.43 in 2007, -0.42 in 2012, -0.36 in 2017 and -0.27 in 2022. For the VCI results, findings revealed that the mean VCI in the basin was 83.73 in 2002, 64.26 in 2007, 56.76 in 2012, 45.32 in 2017, and 14.93 in 2023. Also, the VHI results revealed that the mean VHI in the basin was 75.44 in 2002, 69.54 in 2007, 61.02 in 2010, 37.22 in 2017 and 18.87 in 2022. The study therefore concluded that vegetation is decreasing in the basin, while land surface temperature is increasing.